Research on Mining Development in Yunnan under Ecological Environment Compensation - Jianqun Xiang; Yunzhong Liu; Dan Dong; Meng Zhang (Institute of Advanced Engineering and Science, 2013)
Yunnan province is rich of mineral resources, and the mining industry is the pillar industry in Yunnan. But with the development of mining economy, the problems of the ecological environmental damage have come out. Under the mechanism of ecological environment compensation, the mining economic development in Yunnan needs to deal well with the problems of environmental protection. According to the natural ecological conditions of mining area in Yunnan Province, and combining with the phenomena on economic, social, and environmental development, the paper will analyze the impact on ecological environment in Yunnan in the process of mineral exploitation and utilization. It will also provide the mining development and environmental protection in Yunnan with reasonable proposal and give decision-making references about development plans for government. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2561